The study of 2-acetylaminotoluene ozonolysis in acetic ACID - Галстян, Андрій Генрійович (Eastern-European Journal of Enterprise Technologies, 2014)
The kinetics and mechanism of ozone reaction with 2-aminotoluene and its acylated derivative in acetic acid were studied in order to determine the possibility of obtaining 2-aminobenzoic acid. It is shown that the 2-aminotoluene ozonolysis reaction in acetic acid solution runs at high speed, and preferably on the free electron pair of the amino group to form mainly resinous compounds; oxidation products by the methyl group of the substrate are not formed under these conditions. The ozone attack direction changes towards oxidation of the methyl group and the aromatic ring by N-acylation of the amino group. 2-Acetylaminotoluene reacts with ozone to form mainly degradation products of the aromatic ring - aliphatic peroxides (80.7%), and oxidation products by the methyl group - 2-acetylaminobenzaldehyde at early stages and at deeper stages - 2-aminobenzoic acid (14.0%), which if necessary can easily be hydrolyzed to the corresponding 2-aminobenzoic acid. Ozone is consumed in the reaction in two ways: non-chain ozone consumption mechanism prevails at temperatures of up to 20°C, and chain ozone consumption along with non-chain is observed at higher temperatures. These data will be useful to develop a method of catalytic oxidation of 2- acetylaminotoluene by ozone to the corresponding benzoic acid.